Interrogating Tumor Metabolism and Tumor Microenvironments Using Molecular Positron Emission Tomography Imaging. Theranostic Approaches to Improve Therapeutics - Jacobson, Orit (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Positron emission tomography (PET) is a noninvasive molecular imaging technology that is becoming increasingly important for the measurement of physiologic, biochemical, and pharmacological functions at cellular and molecular levels in patients with cancer. Formation, development, and aggressiveness of tumor involve a number of molecular pathways, including intrinsic tumor cell mutations and extrinsic interaction between tumor cells and the microenvironment. Currently, evaluation of these processes is mainly through biopsy, which is invasive and limited to the site of biopsy. Ongoing research on specific target molecules of the tumor and its microenvironment for PET imaging is showing great potential. To date, the use of PET for diagnosing local recurrence and metastatic sites of various cancers and evaluation of treatment response is mainly based on [(18)F]fluorodeoxyglucose ([(18)F]FDG), which measures glucose metabolism. However, [(18)F]FDG is not a target-specific PET tracer and does not give enough insight into tumor biology and/or its vulnerability to potential treatments. Hence, there is an increasing need for the development of selective biologic radiotracers that will yield specific biochemical information and allow for noninvasive molecular imaging. The possibility of cancer-associated targets for imaging will provide the opportunity to use PET for diagnosis and therapy response monitoring (theranostics) and thus personalized medicine. This article will focus on the review of non-[(18)F]FDG PET tracers for specific tumor biology processes and their preclinical and clinical applications.